Comparação da psicoterapia breve com a utilização da técnica sandplay em mulheres com sintomas depressivos - Afonso, Ana Paula de Toledo (2018)
Depression, better known as "the great evil of the century," has been growing with longer durations, severe signs, and early onset. Females present a higher incidence of pathology than males, and present significant hormonal changes. Today, not only have they entered the labor market, acquiring their long-awaited independence, but also occupying a large part of the professional labor force. With this, the female sex has played new roles, unlike those delegated to them in the past, such as marriage, domestic duties and motherhood. The current context can be stressful and exhausting to the female, especially to a more fragile psyche, which possibly favors depressive pictures. It is human nature to dissatisfaction, misfortune and problems with life and with people. Seeking help often becomes necessary, but it does not have to be costly and long-lasting. There is short-term psychological counseling, which allows for the resolution of difficult conflicts, with more accessible costs and with fewer consultations. Short psychotherapy has been used in an opportune moment, since the health plans only allow the users the psychological treatment with a restricted number of sessions. The present study aims to collaborate with the improvement of the health of women, offering a psychological attention focused on the complaint presented, using an important technique, in a reduced period of time. The sociodemographic questionnaire will be applied, seeking to know the age, socioeconomic and cultural level, religion, number of children and knowledge about the symptoms of major depressive symptoms and the Depressive Thoughts Scale - EPD, in a group of women aged between 18 and 59 years, who were invited or attended spontaneously to the Mandala Psychology Clinic, during the period of June and July of 2017, among the female audience who sought psychological care. Results: After the 12 sessions with the sandplay application, participants were reevaluated with a new application of the Depressive Thoughts Scale - EPD and the main depressive symptoms. Conclusions: It can be concluded that after the brief psychotherapy, there was a positive evolution in the results collected at the beginning of the treatment compared to the results obtained at the end of the treatment.